STUDI KASUS: PENATALAKSANAAN TERAPI KOMPLEMENTER PADA IBU HAMIL TRIMESTER III DENGAN NYERI PUNGGUNG - Viqy Lestaluhu (Jurnal Kebidanan, 2022)
Various problems that arise in the third trimester of pregnancy are problems that are often complained of by pregnant women, such as anxiety and pain. Among these complaints, low back pain is the most commonly reported, occurring in 60% -90% of pregnant women, and is one of the causes of the incidence of cesarean delivery. Back pain is caused by pain in the lumbosacral area. The increase in intensity as the gestational age increases is caused by a shift in the center of gravity and changes in body posture. Back pain from sacroiliac/lumbar can be a long term back problem if not treated immediately. One of the complementary therapies that can reduce or relieve pain, reduce or prevent muscle spasms, provide a sense of comfort, namely with warm compresses and prenatal massage. This case study describes the management of complementary therapy consisting of warm compresses and prenatal massage in third trimester pregnant women with complaints of back pain. After midwifery care was implemented, Mrs. F experienced a decrease in back pain so that the problem could be resolved.